Feasibility of using urinary N7-(2-carbamoyl-2-hydroxyethyl) Guanine as a biomarker for acrylamide exposed workers. (November 2018) - Huang, Yu-Fang; Huang, Chih-Chun; Lu, Chensheng; Chen, Mei-Lien; Liou, Saou-Hsing; Chiang, Su-Yin; Wu, Kuen-Yuh
Abstract Acrylamide (AA), a probable human carcinogen, is a widely-used industrial chemical but is also present in tobacco smoke and carbohydrate-rich foods processed at high temperatures. AA is metabolized to glycidamide (GA) to cause the formation of DNA adducts. N7-(2-carbamoyl-2-hydroxyethyl) guanine (N7-GAG), the most abundant DNA adduct induced by GA, was recently detected in urine of smokers and non-smokers. In this study, we assessed the variability of AA exposure and biomarkers of AA exposure in urine samples repeatedly collected from AA-exposed workers and explored the half-life of N7-GAG. A total of 8 AA-exposed workers and 36 non-exposed workers were recruited. Pre-shift and post-shift urine samples were collected from the exposed group in parallel with personal sampling for eight consecutive days and from the control group on day 1 of the study. Urinary N7-GAG and the mercapturic acids of AA and GA, namelyN -acetyl-S-(2-carbamoylethyl)-L-cysteine (AAMA) andN -(R, S)-acetyl-S-(1-carbamoyl-2-hydroxyethyl)-l -cysteine (GAMA) were analyzed using on-line solid phase extraction-liquid chromatography-electrospray ionization/tandem mass spectrometry methods. We found that N7-GAG levels in urine were significantly higher in exposed workers than in controls and that N7-GAG level correlated positively with AAMA and GAMA levels. Results from this study showed that AAMA and GAMA possibly remain the more preferred biomarkers of AA exposure and that N7-GAG levels could be elevated by occupational exposures to AA and serve as a biomarker of AA-induced genotoxicity for epidemiological studies.